Association between depression screening and sick leave among employees in Serbia: Depression and sick leave in Serbia - Knežević, Snežana; Milasinovic, Jelena; Stojanovic, Roksanda; Milanovic, Snezana; Savic, Dragana; Markulic, Jelena; Stajic, Dalibor (PONS - medicinski časopis, 2025)
Objective. The mental health of employees represents a key factor affecting absenteeism and productivity. This study aimed to examine the association between depressive symptoms and absenteeism among employees in Serbia and to identify demographic and socioeconomic factors influencing this relationship.Methods. A cross-sectional study was conducted using data from the National Health Survey, including a sample of 4,652 employees aged 18-65 years. Descriptive statistics and binary logistic regression, adjusted for demographic and socioeconomic factors, were used to analyze the association between depressive symptoms and absenteeism.Results. The prevalence of mild depressive symptoms was 2.3%, and depressive episodes were 0.6%. Women showed significantly higher prevalence of depressive symptoms compared to men (3.9% vs 2.1%, p=0.002). The most common symptoms were fatigue (2.1%) and sleep problems (1.6%). All depressive symptoms showed a statistically significant association with absenteeism (p
Keywords: working-age population; mental health; depression; prevention; sick leave